Entrepreneurial spawning: Experience, education, and exit - Douglas Cumming; Uwe Walz; Jochen Christian Werth (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
We investigate the career dynamics of high-tech entrepreneurs by analyzing the exit choice of entrepreneurs: to act as a business angel, to found another firm, or to become dependently employed. Our detailed data from CrunchBase indicate that founders are more likely to stick with entrepreneurship as a serial entrepreneur or as an angel investor in cases where the founder had prior experience either in founding other startups or working for a startup, or had a 'jack-of-all-trades' education.
urn:nbn:de:hebis:30:3-392990
Keywords: G24; G34; L26; 330; venture governance; entrepreneurship; entrepreneurial spawning; angel finance; venture capital; exit